(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses the legal aspects of the organization of agricultural production. In addition, provides the legal framework for the regulation of business activity in the field of agriculture, also addresses the issues of business objects in the field of agriculture and their types, the legal status of agricultural production. Key words: agricultural production, agricultural business, agricultural cooperatives, peasant (farmer) economy.